Implementasi Program Keluarga Harapan Pada Masa Pandemi Covid-19 di Kabupaten Kampar Provinsi Riau - Winda Mediana; Hasim As'ari (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
Tambang Sub-district is one of the sub-districts located in Kampar Regency, Riau Province which also established the Covid-19 Pandemic with the current number of PKH recipients as many as 1,804 Beneficiary Families (KPM). This study aims to determine the implementation of the Program Keluarga Harapan (PKH) during the Corona Virus Disease 2019 (Covid-19) Pandemic in Tambang District, Kampar Regency and the inhibiting factors for the implementation of the Program Keluarga Harapan (PKH) during the Corona Virus Disease 2019 (Covid-19) Pandemic. ) in the Mine District, Kampar Regency. The concepts used by researchers are policy theory, policy implementation theory, and the concept of the Program Keluarga Harapan (PKH). The research method used is qualitative using a descriptive case study method with data collection techniques through interviews and documentation. The results of this study indicate that the implementation of the Program Keluarga Harapan (PKH) during the Corona Virus Disease 2019 (Covid-19) Pandemic in Tambang District, Kampar Regency is carried out by applying standards and targets, resources, relationships between organizations, characteristics of implementing agents, social environmental conditions. and economics and disposition of implementers. Then there are also inhibiting factors for the implementation of the Program Keluarga Harapan (PKH) during the Corona Virus Disease 2019 (Covid-19) Pandemic in Tambang District, Kampar Regency, namely the invalid PKH KPM data during the Covid-19 period, adjustments and calculations for PKH assistance during the Covid-19 period. 19 have not fully provided benefits, KPM PKH has difficulty accessing Health Facilities (Faskes) and Education Facilities (Fasdik) during the Covid-19 period, socialization of PKH policies during the Covid-19 period has not been effective, Standard Operational Procedures (SOP) for reporting problems of KPM PKH which intersect with the unstructured BPNT and problematic KPM PKH administration data in e-PKH.Keywords: Implementationi, Program Keluarga Harapan (PKH)